TJNPR 2022
DOI: 10.26538/tjnpr/v6i9.4
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents and Pharmacological Activities of Globimetula braunii (Loranthaceae): A Review

Abstract: Globimetula braunii (Loranthaceae) is a hemiparasitic shrub that grows on dicotyledonous trees; the plant is used traditionally in the treatment of various diseases. This study aims to review the ethnomedicinal uses, scientific and pharmacological studies as well as phytochemistry of G. braunii. Information related to the ethnomedicinal uses, scientific and pharmacological studies as well as phytochemistry of the G. braunii was obtained by searching using the keyword G. braunii in the following databases; Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A total of 128 fractions were collected. The fractions were pooled together based on their TLC profiles to give 21 major fractions coded A-U [6]. Fraction R was further subjected to repeated gel filtration with Sephadex LH-20 and eluted with 100% methanol to afford compound GB5 (7 mg).…”
Section: Extraction and Isolation Of The Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 128 fractions were collected. The fractions were pooled together based on their TLC profiles to give 21 major fractions coded A-U [6]. Fraction R was further subjected to repeated gel filtration with Sephadex LH-20 and eluted with 100% methanol to afford compound GB5 (7 mg).…”
Section: Extraction and Isolation Of The Compoundmentioning
confidence: 99%
“…The plant was reported to contain several secondary metabolites that are responsible for its therapeutic activity [5]. In our previous studies, we reported the isolation of flavonols (rhamnetin, quercetin and rhamnetin-3-O-α-Lrhamnopyranoside) from this plant [6]. This study aimed to isolate more flavonoid compounds present in the n-butanol fraction of the ethanol leaf extract of the plant.…”
Section: Introductionmentioning
confidence: 99%